Analysis and mitigation of voltage measurement errors for three-phase parallel voltage source inverters - Qi, Yang (2019)
In islanded microgrids, distributed generations (DGs) have been increasingly employed through voltage source inverters (VSIs). When multiple VSIs operate in parallel, it is important to properly share the load power among them. This paper reveals that voltage measurement errors may deteriorate the power-sharing performance by injecting both positive- and negative-sequence circulating currents. To solve this problem, a combined feedforward and feedback voltage control scheme is proposed. Specifically, the feedforward control is utilized to attenuate the negative impact caused by voltage measurement errors, while the feedback control is adopted for the harmonic mitigation. One salient advantage is that the proposed control scheme is fully decentralized and hence does not require any communications among DGs. Finally, Hardware-in-loop (HIL) simulation results are provided for verification.